Quinone outside inhibitor fungicides combine with salicylhydroxamic acid to inhibit leaf spotting fungi from hydroponic lettuce for sensitivity in vitro test - Kongtragoul, Pornprapa; Junpatiw Ahuja, Anjana (วารสารแก่นเกษตร, 2021)
Hydroponics is a popular alternative to conventional growing approaches in Thailand, and many farmers use this method, especially to grow lettuce. Several different types are common: green oak, red oak, butterhead, red coral, and frillice iceberg. However, outdoor hydroponics in tropical zone presents a problem for farmers due to the fungal disease known as leaf spot. Prevent treatments used for leaf spots include a class of fungicides categorized as quinone outside inhibitor (QoI) fungicides. The principal types are trifloxystrobin (TF), azoxystrobin (AZ), and pyraclostrobin (PR). This study visited commercial hydroponics operations and took 17 fungal pathogen isolates from lettuce plants exhibiting leaf spot disease. Among these isolates, there were 9, 5, 2, and 1 isolates of Cercospora sp., Corynespora cassiicola, Curvularia sp., and Alternaria sp., respectively. The inhibition of mycelial respiration on potato dextrose agar (PDA) as a consequence of the combined effect of TF, AZ, and PR with salicylhydroxamic acid (SHAM) were evaluated with the classification of the levels of sensitivity based on 50% effective concentrations (EC50). The SHAM reaction demonstrated synergism in each of the tested fungicides with a synergy factor greater than 1. In the case of the two isolates of C. cassiicola, a high degree of resistance (HR) was reported with the isolated code as RO_PT012 to TR, AZ, and PY, and isolate RO_PT013 to AZ and TR, with an EC50 value above 100 mg/l. Furthermore, a majority of the fungal isolates were categorized as sensitive (S) to the QoI fungicides tested, having EC50 values lower than 10 mg/l. Therefore, it was concluded that SHAM showed a synergistic effect with the QoI fungicide, which was significant while assessing the level of QoI sensitivity under in vitro testing.